Religiosity and posttraumatic growth: a note concerning the problems of confounding in their measurement and the inclusion of religiosity within the definition of posttraumatic growth - Joseph, Stephen (Mental health, religion & culture, 2011)
The aim of this comment is to: (1) draw researcher's attention to the problem of confounding in studies assessing both religiosity and posttraumatic growth; and (2) call for research to separately investigate spirituality in the aftermath of trauma rather than as part of the posttraumatic growth construct.